(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This review explores the fundamental concepts and developmental aspects of Diabetes Mellitus (DM) and its intricate association with Diabetic Cardiomyopathy (DCM). Diabetes Mellitus, a chronic metabolic disorder, is examined in terms of its etiology, classifications, and impact on cardiovascular health, leading to the development of Diabetic Cardiomyopathy. The abstract also delves into the underlying mechanisms linking DM and DCM, emphasizing the importance of early detection, prevention, and comprehensive management strategies to mitigate cardiovascular complications. A comprehensive exploration of the underlying mechanisms linking DM and DCM is presented. This includes detailed insights into insulin resistance, microvascular dysfunction, myocardial fibrosis, mitochondrial dysfunction, and impaired calcium handling, all contributing to the structural and functional changes observed in DCM. In conclusion, this abstract shed light on the intricate relationship between Diabetes Mellitus and Diabetic Cardiomyopathy. Understanding the mechanisms underlying the development of DCM provides a foundation for early detection, prevention, and management strategies. A holistic approach encompassing medical interventions, lifestyle modifications, and interdisciplinary collaboration is pivotal in minimizing the impact of DM on cardiovascular health and improving the quality of life for affected individuals